1997
DOI: 10.1016/s0014-5793(97)00181-6
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of tyrosine aminotransferase (TAT) via the ubiquitin–proteasome pathway

Abstract: Most of the known cellular substrates of the ubiquitin system are short‐lived growth regulators and transcriptional activators. Very few enzymes involved in intermediary metabolism have been shown to be targeted by the system. In a reconstituted cell‐free system, we show that tyrosine aminotransferase (TAT), a key enzyme involved in amino acid metabolism, is conjugated and degraded in an ATP‐ and ubiquitin‐dependent manner. Degradation of ubiquitin–TAT adducts requires, in addition to the 26S proteasome, a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…19) PLP can bind lysine residues by schiff base to affect protein properties. Since ubiquitination also occurs on lysine residues, PLP may hide lysine residues representing polyubiquitination sites on proteins, thereby preventing ubiquitin-mediated protein degradation and prolonging protein activity in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…19) PLP can bind lysine residues by schiff base to affect protein properties. Since ubiquitination also occurs on lysine residues, PLP may hide lysine residues representing polyubiquitination sites on proteins, thereby preventing ubiquitin-mediated protein degradation and prolonging protein activity in the cell.…”
Section: Discussionmentioning
confidence: 99%
“…In hTAT, the first 38 amino acids may not be involved in enzyme dimerization, and are not required in the active site stability and enzyme-substrate interactions (Sobrado et al, 2003). This N-terminal fragment, however, is required for being targeted by the ubiquitin-proteosome pathway (Gross-Mesilaty et al, 1997), which degrades proteins to small peptides (Ciechanover et al, 2000). So far crystal structures of TATs from Escherichia coli (Ko et al, 1999), T. cruzi (Blankenfeldt et al, 1999), and Homo sapiens (Protein Data Bank code, 3dyd) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this pathway regulates the processing of MHC class I-restricted antigens [Rock et al, 1994], and metabolic enzymes such as tyrosine amino transferase (TAT) and Cu/Zn superoxide dismutase [Hoffman et al, 1996;Gross-Mesilaty et al, 1997]. Several cell cycle protein substrates are also degraded by the proteasome including p21, p27, p53, and cyclins [Scheffner et al, 1990;Glotzer et al, 1991;Pagano et al, 1995].…”
mentioning
confidence: 99%